Experimental myocardial hypertrophy induced by a minimally invasive ascending aorta coarctation - Martins, A.S. [UNESP]; Aguilera, N.W. [UNESP]; Matsubara, B.B. [UNESP]; Bregagnollo, Edson Antônio [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2001)
Ascending aorta coarctation was produced by a minimally invasive technique in rabbits. Animal mortality was 5%. Morphometric and hemodynamic parameters were evaluated. A parabiotically isolated heart model was used to assess the hemodynamic parameters. Left ventricular weight/body weight ratio and muscle area showed clear evidence of hypertrophy when compared to control. The hemodynamic changes in the isolated heart model suggested decreased diastolic and systolic function in the coarcted group. The present model produced hypertrophy with low mortality rates as a result of its less invasive nature.
Keywords: ventricular hypertrophy; ventricular function; experimental model